Identification and characterization of xanthone biosynthetic genes contributing to the vivid red coloration of red‐flowered gentian. (10th August 2021) - Sasaki, Nobuhiro; Nemoto, Keiichirou; Nishizaki, Yuzo; Sugimoto, Naoki; Tasaki, Keisuke; Watanabe, Aiko; Goto, Fumina; Higuchi, Atsumi; Morgan, Ed; Hikage, Takashi; Nishihara, Masahiro
Summary: Cultivated Japanese gentians traditionally produce vivid blue flowers because of the accumulation of delphinidin‐based polyacylated anthocyanins. However, recent breeding programs developed several red‐flowered cultivars, but the underlying mechanism for this red coloration was unknown. Thus, we characterized the pigments responsible for the red coloration in these cultivars. A high‐performance liquid chromatography with photodiode array analysis revealed the presence of phenolic compounds, including flavones and xanthones, as well as the accumulation of colored cyanidin‐based anthocyanins. The chemical structures of two xanthone compounds contributing to the coloration of red‐flowered gentian petals were determined by mass spectrometry and nuclear magnetic resonance spectroscopy. The compounds were identified as norathyriol 6‐ O ‐glucoside (i.e., tripteroside designated as Xt1) and a previously unreported norathyriol‐6‐ O ‐(6′‐ O ‐malonyl)‐glucoside (designated Xt2). The copigmentation effects of these compounds on cyanidin 3‐ O ‐glucoside were detected in vitro . Additionally, an RNA sequencing analysis was performed to identify the cDNAs encoding the enzymes involved in the biosynthesis of these xanthones. Recombinant proteins encoded by the candidate genes were produced in a wheat germ cell‐free protein expression system and assayed. We determined that a UDP‐glucose‐dependent glucosyltransferase (StrGT9) catalyzes the transfer of a glucose moiety to norathyriol, a xanthone aglycone, to produce Xt1, which is converted to Xt2 by a malonyltransferase (StrAT2). An analysis of the progeny lines suggested that the accumulation of Xt2 contributes to the vivid red coloration of gentian flowers. Our data indicate that StrGT9 and StrAT2 help mediate xanthone biosynthesis and contribute to the coloration of red‐flowered gentians via copigmentation effects. Significance Statement: We identified two key genes encoding UDP‐glucose‐dependent glucosyltransferase and malonyl‐CoA acyltransferase, which are involved in xanthone biosynthesis in red‐flowered gentian. In vitro assays involving different pigment combinations demonstrated that a malonylated tripteroside synthesized from norathyriol via these two enzymes increases the absorption of cyanidin 3‐ O ‐glucoside, and a progeny line analysis suggested that the presence of malonylated tripteroside is associated with the vivid red coloration of gentian flowers.